Pembelajaran Kalam Berbasis Phonetic Accuracy untuk Meningkatkan Kemampuan Berbicara Bahasa Arab - Kholisin, Kholisin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This study aims to develop a teaching and learning model of kalam (conversation) based on phonetic accuracy to improve students’ Arabic speaking ability. The research was conducted through questionnaires, interviews, error analysis, and content analysis. The results of the study are as follows: there are two forms of phonetic errors in students’ pronunciation, namely segmental and suprasegmental errors; most teachers and students did not pay attention to phonetic errors in students’ speech; however, most of them considered it important to place special emphasis on phonetic elements in learning kalam; the kalam teaching materials used thus far did not specifically emphasize phonetic accuracy; and both teachers and students suggested that kalam textbooks should include special training in phonetic accuracy and that such training should be introduced at an early stage. Based on these findings, a teaching and learning model of kalam needs to be developed.